Drug-related adverse events potentially predict the efficacy of apatinib on advanced hepatocellular carcinoma - Xiaoying Gu; Su Zhang; Xuejiao Yang; Tao Guan; Zhenyu Hou; Manqing Cao; Huikai Li; Ti Zhang (BMC Gastroenterology, 2022)
Abstract Background Hepatocellular carcinoma (HCC) is the fourth leading cause of cancer-related deaths worldwide every year, and most HCC patients are diagnosed with advanced disease and can only receive systemic treatment. TKIs are the most important components of the systemic treatment of HCC and have both good efficacy and adverse events (AEs).  Methods This analysis included 207 patients with locally advanced unresectable or metastatic HCC who received oral treatment with apatinib. We analyzed the overall survival (OS) and progression-free survival (PFS) of patients with or without corresponding AEs to evaluate which AEs can predict the efficacy of apatinib. Results Patients with hand-foot syndrome (HFS; p = 0.005), proteinuria (p = 0.006) and diarrhea (p < 0.001) had significantly better OS than those without corresponding AEs, and the appearance of HFS (p = 0.006) and proteinuria (p = 0.004) was associated with longer PFS. Conclusion Among all the AEs induced by apatinib in the treatment of advanced HCC, proteinuria could potentially predict PFS, and diarrhea was a potential predictor of OS.